2009
DOI: 10.1016/j.febslet.2009.10.081
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavins retard human breast cancer cell migration by inhibiting NF‐κB via p53‐ROS cross‐talk

Abstract: Edited by Quan Chen Keywords:Breast cancer Migration NF-jB p53 Reactive oxygen species Theaflavins a b s t r a c tThe present study demonstrates that theaflavins exploit p53 to impede metastasis in human breast cancer cells. Our data suggest that p53-dependent reactive oxygen species (ROS) induce p53-phosphorylation via p38MAPK in a feedback loop to inhibit IjBa-phosphorylation and NF-jB/p65 nuclear translocation, thereby down-regulating the metastatic proteins metalloproteinase (MMP)-2 and MMP-9. When wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…The naturally occurring inhibitors of MMP activity (TIMPs) were preferential to be considered for the development of anticancer agents. 30) Several MMP inhibitors have been identified from natural sources such as resveratrol, 31) theaflavins, 32) catechins, 33) curcumin [34][35][36] and genistein. 37) In this study, we showed that anethole inhibited the activity of MMP-2 and -9 and simultaneously increased the activity of TIMP-1 in HT 1080 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The naturally occurring inhibitors of MMP activity (TIMPs) were preferential to be considered for the development of anticancer agents. 30) Several MMP inhibitors have been identified from natural sources such as resveratrol, 31) theaflavins, 32) catechins, 33) curcumin [34][35][36] and genistein. 37) In this study, we showed that anethole inhibited the activity of MMP-2 and -9 and simultaneously increased the activity of TIMP-1 in HT 1080 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The data from triplicate wells were calculated as the mean +/− SEM. The migration rate of control cells was taken as 100% and that of other plates were compared with control cells [25].…”
Section: Methodsmentioning
confidence: 99%
“…For the assessment of cellular ROS, cultured cells or sensitive as well as resistant EAC cells, aseptically drawn within 2 h of drug treatment from the peritoneal cavity of tumor-bearing mice, were incubated for 20 min at 37 °C in the dark with 10  μ M of dichlorofluorescindiacetate (DCFH-DA, Sigma). 48 DCF fluorescence was measured flow cytometrically (Beckton Dickinson FACScan) and subjected to analysis using Cell Quest 3.2 (Beckton Dickinson) software. The probe was excited at 488 nm, and emission was measured through a 530 nm band-pass filter.…”
Section: Methodsmentioning
confidence: 99%